2015
DOI: 10.1016/j.bbamcr.2015.07.025
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of superoxide dismutase 1 by PMA is involved in cell fate determination and mediated via protein kinase D2 in myeloid leukemia cells

Abstract: Myeloid leukemia cells maintain a high intracellular ROS level and use redox signals for survival. The metabolism of ROS also affects cell fate, including cell death and differentiation. Superoxide dismutases (SODs) are major antioxidant enzymes that have high levels of expression in myeloid leukemia cells. However, the role of SODs in the regulation of myeloid leukemia cells' biological function is still unclear. To investigate the function of SODs in myeloid leukemia cell death and differentiation, we used m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 63 publications
(67 reference statements)
2
8
0
Order By: Relevance
“…The results in tables (4) and (5) showed that there was a significant increase (p<0.05) in superoxide dismutase activity in CSF of acute lymphoblastic leukemia patients in both sexes and for all age group, our result was in agreement with previous studies which showed a significant increase in SOD activity In serum for patients with Chronic myeloid leukemia (CML) [50] and acute myeloid leukemia (AML) [51] and in CSF of children with neurocysticercosis [52] . The most efficient enzymatic antioxidants is superoxide dismutase (SOD), SOD activity protects cells from free radicals induced injury by catalyzing the dismutation of O -to O and to the less-reactive species hydrogen peroxide (H 2 O 2 ) [53] .…”
Section: Superoxide Dismutase (Sod)supporting
confidence: 82%
“…The results in tables (4) and (5) showed that there was a significant increase (p<0.05) in superoxide dismutase activity in CSF of acute lymphoblastic leukemia patients in both sexes and for all age group, our result was in agreement with previous studies which showed a significant increase in SOD activity In serum for patients with Chronic myeloid leukemia (CML) [50] and acute myeloid leukemia (AML) [51] and in CSF of children with neurocysticercosis [52] . The most efficient enzymatic antioxidants is superoxide dismutase (SOD), SOD activity protects cells from free radicals induced injury by catalyzing the dismutation of O -to O and to the less-reactive species hydrogen peroxide (H 2 O 2 ) [53] .…”
Section: Superoxide Dismutase (Sod)supporting
confidence: 82%
“…The knockdown of SOD1 in nasopharyngeal carcinoma cells reduced its growth and induced apoptosis [25]. SOD1 regulates cell death and differentiation in myeloid leukemia cell lines K562, MEG-01, TF-1, and HEL [44]. Additionally, the inhibition or silencing of SOD1 increased the cell death induced by PMA (phorbol 12-myristate 13-acetate).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the catalase-dependent reduction of mitochondrial ROS controls immune cell proliferation. Similarly, the inhibition of the free radical scavenger Cu, Zn superoxide dismutase (SOD1), which is co-imported into mammalian peroxisomes with a copper chaperone [46], led to cell proliferation arrest and the promotion of cell death in myeloid leukemia cells [47]. Nevertheless, SOD1 is mainly cytosolic and just 0.15% localized inside the peroxisome [46] and there is no evidence for a specific role of peroxisomal SOD1 in this pathology.…”
Section: The Regulation Of Peroxisomal Genes Is Correlated To Prolmentioning
confidence: 99%